ANALYSIS OF GOING CONCERN FACTORS FOR COMPANIES - Catur Fatchu Ukhriyawati; Sam Feri Purwanto; Edwin Agung Wibowo; Rahman Hasibuan; Oktavianti Oktavianti (International Conference on Business Management and Accounting, 2022)
This study aims to determine the effect of financial distress, profitability, leverage, liquidity and company growth on going concern audit opinions companies in the 2018-2021 period listed on the Indonesia Stock Exchange. Purposive sampling was used as a sample selection method. So that there are 228 samples of company data listed on the Indonesia Stock Exchange for the 2018-2021 period. Logistic regression is used as a method of data analysis because the dependent variable uses a dummy variable as a measuring instrument. The results show that financial distress has an effect on going concern, profitability has an effect on going concern, leverage has an effect on going concern, liquidity has an effect on going concern and growth has an effect on going concern.